PERAN RELAWAN PALIATIF DALAM PERAWATAN PALIATIF PASIEN STROKE - TRIANANG MARWOKO (LPPMK STIKES Widyagama Husada, 2022)
Abstract Palliative care is a form of service that aims to improve the quality of life of patients and families from life-threatening diseases. With good knowledge, the role of volunteers in providing palliative care services to patients and their families will be better. This study aims to describe the role of palliative volunteers in the palliative care of stroke patients in Batu City. The population in this study are volunteers who are members of the membership. Determination of the number of samples used is purposive sampling which is determined and selected with certain considerations and goals. Methods of data collection through observation, documentation and interviews. The results showed that the role of volunteers in patient self-care, especially in meeting the basic needs of life, could improve the quality of life of patients. Through mentoring provided by volunteers, especially in counseling, it plays a very important role in reducing the level of patient anxiety so that patients no longer think about the cost of their care because the volunteers have sought assistance or sources of treatment funds.